2005
DOI: 10.1088/0031-9155/50/7/017
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of respiration-correlated PET and CT scans: correlated lung tumour motion in anatomical and functional scans

Abstract: Lower lobe lung tumours in particular can move up to 2 cm in the cranio-caudal direction during the respiration cycle. This breathing motion causes image artefacts in conventional free-breathing computed tomography (CT) and positron emission tomography (PET) scanning, rendering delineation of structures for radiotherapy inaccurate. The purpose of this study was to develop a method for four-dimensional (4D) respiration-correlated (RC) acquisition of both CT and PET scans and to develop a framework to fuse these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 18 publications
1
63
0
1
Order By: Relevance
“…For each region of interest, alignment to the end exhale state of each session was performed using a 3-D regional rigid alignment tool for translation and rotation developed at the Netherlands Cancer Institute. 16 The alignment was reviewed visually on the axial, coronal, and sagittal planes (Figure 1b) to verify the goodness-of-fit based on anatomy within that ROI. The displacement as a function of breath-hold state was determined for a reference point placed approximately in the center of each region of interest on the exhale dataset.…”
Section: Methodsmentioning
confidence: 99%
“…For each region of interest, alignment to the end exhale state of each session was performed using a 3-D regional rigid alignment tool for translation and rotation developed at the Netherlands Cancer Institute. 16 The alignment was reviewed visually on the axial, coronal, and sagittal planes (Figure 1b) to verify the goodness-of-fit based on anatomy within that ROI. The displacement as a function of breath-hold state was determined for a reference point placed approximately in the center of each region of interest on the exhale dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 illustrates the imaging artifact that can occur when a 4D PET image is corrected using CTAC data which is out of phase of the 4D PET data. While it has been reported that it is feasible to minimize motion artifacts by using 4D PET corrected by 4D CT in patients in a clinical setting, ( 21 23 ) the addition of a 4D CT adds considerable complexity, as well as increased patient dose. As a consequence, clinical centers may avoid these complications by using 4D PET imaging protocols with attenuation correction based on 3D CT. A number of studies have compared different methods for 4D PET attenuation correction in patients ( 21 ) and phantoms, ( 24 26 ) as well as simulated data based on 3D PET and 4D CT in patients.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this shortcoming, several techniques such as respiration-correlated acquisitions have been proposed (10)(11)(12)(13)(14)(15)(16)(17). In respiration-correlated PET (RCPET)/CT (RCCT), the patient's respiratory signal is recorded during the acquisition of the data.…”
mentioning
confidence: 99%
“…In respiration-correlated PET (RCPET)/CT (RCCT), the patient's respiratory signal is recorded during the acquisition of the data. Many studies have shown the benefit of respiration-correlated PET for a fixed number of phases in terms of improved volume recovery and SUV quantification for moving tumors (11,12,15,17).…”
mentioning
confidence: 99%